Fungal Gummosis in Peach - Sara Sherman; Mercy Olmstead; Philip Harmon; Thomas Beckman (EDIS)
Fungal gummosis in peach occurs when the fungus Botryosphaeria dothidea infects small openings or wounds in tree branches or trunks. The disease causes blisters on the tree that form lesions and eventually ooze gum (sap). This 3-page fact sheet covers the disease cycle and management of fungal gummosis in peach, which is often difficult to control. Written by Sara Sherman, Mercy Olmstead, Philip Harmon, and Thomas Beckman, and published by the UF Department of Horticultural Sciences, July 2015.